Braf protein mutation and its significancy within patients with melanoma - Julia Kuchnicka; Aleksandra Kuchnicka; Katarzyna Kosz; Klaudia Remjasz; Natalia Zarankiewicz; Martyna Zielińska; Klaudia Sapuła; Jakub Aleksandrowicz; Wojciech Siedlecki (Kazimierz Wielki University, 2022)
Introduction and purpose:   This review aims to analyze BRAF mutation significancy and its influence on progression and therapy methods within patients with melanoma.  Material and method:  This review was mainly based on articles collected in Pubmed in years 2004-2018. The research was done by looking through keywords as follows "braf kinase", "braf mutation", "melanoma" "wemurafenib".  Results:  The selected studies have demonstrated that it is justified to identify patient with BRAF mutation due to it's influence on treatment's method choosing.  Conclusions:  Citied researches have proven BRAF mutation significancy in growth and progressions of many malignant tumors. Further tests are likely to not only prolong life expectancy within patients with melanoma, but also being a source of crucial knowledge about tumors development.